Accounting Disclosures and the Market's Valuation of Oil and Gas Properties. - Harris, Trevor S.; Ohlson, James A. (The Accounting Review, 1987)
Abstract ABSTRACT: This paper Investigates the explanatory power of various measures that indicate the value of a firm's oil and gas properties. The empirical method relies on cross-sectional valuation models applied over the 1979-83 period. The evidence demonstrates that the primary statements' net book value data are highly significant in explaining the market value of oil and gas properties. This measure dominates the supplementary valuation measures supplied in firms' footnotes, including the "standardized present value" measure. The evidence also clearly shows that the market distinguishes rationally between the successful efforts and the full cost accounting methods.